Mechanically‐Reconfigurable Edge States in an Ultrathin Valley‐Hall Topological Metamaterial. Issue 26 (18th August 2022) - Liu, Yahong; Ren, Huiling; Tao, Liyun; Du, Lianlian; Zhou, Xin; Li, Meize; Song, Kun; Ji, Ruonan; Zhao, Xiaopeng; Navarro‐Cía, Miguel
Abstract: Broadband topological metamaterials hold the key for designing the next generation of integrated photonic platforms and microwave devices given their protected back‐scattering‐free and unidirectional edge states, among other exotic properties. However, synthesizing such metamaterial has proven challenging. Here, a broadband bandgap (relative bandwidth of more than 43%) Valley‐Hall topological metamaterial with deep subwavelength thickness is proposed. The present topological metamaterial is composed of three layers printed circuit boards whose total thickness is 1.524 mm ≈ λ/100. The topological phase transition is achieved by introducing an asymmetry parameter δr . Three mechanically reconfigurable edge states can be obtained by varying interlayer displacement. Their robust transmission is demonstrated through two kinds of waveguide domain walls with cavities and disorders. Exploiting the proposed topological metamaterial, a six‐way power divider is constructed and measured as a proof‐of‐concept of the potential of the proposed technology for future electromagnetic devices. Abstract : A broadband bandgap Valley‐Hall topological metamaterial with deep subwavelength thickness is proposed. The present topological metamaterial is composed of three layers printed circuit boards whose total thickness is about λ/100. The topological phase transition is achieved by introducing an asymmetry parameter. Three mechanically reconfigurable edge states can be obtained by varying interlayer displacement. It is demonstrated that the robust transmission can be achieved through two kinds of waveguide domain walls with cavities and disorders.